National School-Based Health Lifestyles Intervention in Chinese Children and Adolescents on Obesity and Hypertension - Yanhui Dong; Zhiyong Zou; Haijun Wang; Bin Dong; Peijin Hu; Yinghua Ma; Yi Song; Jun Ma (Frontiers Media S.A., 2021)
Introduction: This study aimed to examine the effectiveness of the national school-based intervention on both obesity and high blood pressure in Chinese children and adolescents aged 6-18 years.Methods: The national school-based cluster non-randomized controlled trial was done in seven provinces from September 2013 to February 2014. A total of 23,175 children and adolescents in the control group and 25,702 in the intervention group were included in this trial with a mean follow-up of 6.7 ± 0.9 months. Mixed-effects regression models were used to evaluate the effect of the interventions on body weight and blood pressure (BP).Results: A significant upward in the body mass index (BMI) levels but downward in systolic BP (SBP), diastolic BP (DBP), BMI Z-scores, SBP Z-scores, and DBP Z-scores were witnessed in the intervention group compared to those in the control group (<0.001). Subgroup analyses presented significant intervention effects in children aged 6-12 years for BMI, SBP, DBP, and their standardized values Z-scores, but no effective results were found in adolescents aged 13-18 years. Stratification analyses based on the dynamic weight changes presented non-differential HBP, SHBP, and DHBP prevalence gaps between the control and intervention groups. Children aged 6-12 years with higher BMI percentiles at baseline presented obvious declines in SBP and DBP standardized values Z-scores.Conclusion: A mean 6-month multi-centered school-based comprehensive obesity intervention in China yields a small to null effect on obesity and hypertension with increasing age; the early age before 12 years may be the key period for interventions, and the younger, the better. Precise and high-intensity interventions targeting the population at different stages of childhood and adolescence are urgently needed to be developed.Clinical Trial Registration:https://www.clinicaltrials.gov/, identifier: NCT02343588